ANALISIS KESENJANGAN KUALITAS PELAYANAN TERHADAP PENGUNJUNG PERPUSTAKAAN UNIVERSITAS DIPONEGORO - Dedy Douglas Harianja; Rita Rahmawati; Moch. Abdul Mukid (Jurnal Gaussian, 2015)
Good quality service is not based on the perception of the service provider, but based on the perception of service users. If the service received exceed the expectations of users, the quality of service perceived as an ideal quality. This study aimed to analyze the quality of service to visitors to Diponegoro University library based on five variables dimensions of service quality (Service Quality), namely Tangibels, Reliability, Responsiveness, Assurance, and Empathy. Collecting data in this study using a questionnaire distributed to 97 students as respondents. The sampling method used was accidental sampling sampling method. The data obtained and analyzed using Importance Performance Analysis (IPA) and the Customer Satisfaction Index (CSI). Based on this research, calculations showed that all Service Quality indicator variable is negative, which means that all services provided is still below the expectations of library visitors. While the Cartesian diagram shows that there are four indicator variables are in quadrant Concentrate Here is the complete collection, ease of finding references, employee awareness of the needs of visitors, and the friendliness and courtesy of service that means should gradually be corrected immediately. Value Customer Satisfaction Index (CSI) of 72% which means that the overall level of visitor satisfaction is the criterion satisfied. Keywords: Service Quality, Importance Performance Analysis, Customer Satisfaction Index